Determination of Real COD in Highly Chlorinated Wastewaters - Sara, Arslan; Goncaloglu, Buelent Ilhan (WILEY-V C H VERLAG GMBH, 2008)
In order to determine the interference caused by chloride ions in Chemical Oxygen Demand (COD) measurements, synthetically prepared samples with various COD and chloride concentrations were analyzed. In addition, statistical analyses of the results were performed to calculate the real COD caused by the presence of organic substances in chlorinated wastewaters. The results of regression analyses showed good correlation between chloride concentrations and COD levels. A mathematical model is proposed on the basis of the statistical analyses. To calculate the real COD value of a wastewater sample, firstly, the chloride and interfered (or apparent) COD concentrations should be measured and then interference due to the chloride is calculated using the model equation proposed in this study. The real COD value was found by subtracting the COD due to chloride from the apparent COD. The reliability of the proposed model was also validated on real domestic wastewater samples, which were mixed with real seawater in various volumetric ratios to generate a range of salinity concentrations. These real saline samples gave good estimates of real COD with the results indicating that the proposed model can be used with acceptable confidence.
Keywords: Chloride inhibition; Chloride interference; Chemical Oxygen Demand (COD); Wastewater; CHEMICAL OXYGEN-DEMAND; RAPID-DETERMINATION; SYSTEM; Science & Technology - Other Topics; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources